2019
DOI: 10.21037/atm.2019.11.26
|View full text |Cite
|
Sign up to set email alerts
|

Use of radiomic features and support vector machine to distinguish Parkinson’s disease cases from normal controls

Abstract: Background: Parkinson's disease (PD) is an irreversible neurodegenerative disease. The diagnosis of PD based on neuroimaging is usually with low-level or deep learning features, which results in difficulties in achieving precision classification or interpreting the clinical significance. Herein, we aimed to extract highorder features by using radiomics approach and achieve acceptable diagnosis accuracy in PD. Methods: In this retrospective multicohort study, we collected 18 F-fluorodeoxyglucose positron emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 66 publications
1
46
1
Order By: Relevance
“…In our results, the diagnostic efficiency of the radiomic biomarker based on MRI was 83.8%, much higher than the value for other nonmotor symptoms. Nonetheless, the diagnostic efficiency of radiomic biomarkers was lower in the present study than that the study by Wu et al (2019), who showed that the diagnostic efficiency of radiomic biomarkers based on 18F-FDG PET images was 90.97%. However, because PET is not widely used in routine Integrative nomogram used to detect PD.…”
Section: Discussioncontrasting
confidence: 91%
“…In our results, the diagnostic efficiency of the radiomic biomarker based on MRI was 83.8%, much higher than the value for other nonmotor symptoms. Nonetheless, the diagnostic efficiency of radiomic biomarkers was lower in the present study than that the study by Wu et al (2019), who showed that the diagnostic efficiency of radiomic biomarkers based on 18F-FDG PET images was 90.97%. However, because PET is not widely used in routine Integrative nomogram used to detect PD.…”
Section: Discussioncontrasting
confidence: 91%
“…As once said by Robert Gilles et al, “Images are more than pictures, they are data” (Gillies et al., 2016) radiomic approaches based on data‐characterization algorithms have been widely applied to disease prediction and diagnosis especially in oncology and genetic fields. A random forest‐based radiomics analysis combining both nonimaging and imaging variables found the longitudinal DAT‐SPECT images significantly improved the prediction accuracy of PD, and exhibited great potentials toward development of effective prognostic biomarkers in PD (Wu et al., 2019). In recent years, a computer‐based technique utilizing CNN (Ortiz et al., 2019; Shinde et al., 2019) to create prognostic and diagnostic biomarkers has been widely adopted and attracted lots of attention.…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in the multivariate interpretation of neuroimaging data have already been proven useful in a plethora of neuropsychiatric [16] and neurodegenerative diseases [11,12]. Besides, the employment of machine-learning algorithms to Parkinson's disease datasets has offered unique advancements in interpreting distinct neuroimaging modalities [3,4,20,23]. MKL also yields the opportunity to concatenate different imaging modalities.…”
Section: Introductionmentioning
confidence: 99%